The Effect of Isobutyl Paraben an Endocrine Disrupting Chemicals on Juvenile Male Rats (The Review of Diabetic Studies, 2025)
Background:Isobutyl paraben (IBP) is a commonly used preservative with recognized estrogenic activity and potential endocrine-disrupting effects. Despite its widespread exposure, limited data exist on its impact during juvenile development, a critical period of male reproductive maturation.Methods:Juvenile male Wistar rats were administered IBP orally at 10, 20, and 50 mg/kg/day for 70 days, with corn oil as the vehicle control. Endpoints included clinical observations, growth performance, food intake, functional observation battery, hematological and biochemical profiling, organ weight analysis, and histopathology of reproductive and systemic organs.Results:IBP exposure resulted in dose-dependent suppression of body weight gain and food consumption, alongside delayed preputial separation. Hematological findings revealed significant reductions in leukocyte counts, while clinical chemistry demonstrated altered glucose levels, dyslipidemia, and elevations in hepatic enzyme activity. Organ weight assessments indicated significant changes in kidneys, liver, testes, and spleen. Histopathological evaluation confirmed degenerative changes in testicular tissue and epididymis, particularly at higher doses.Conclusion:Sub chronic IBP exposure during the juvenile period disrupts growth, metabolism, and male reproductive development, underscoring its endocrine-disrupting potential and raising concerns regarding long-term health risks